The Implementation Significant of Images and Texts in Students’ Power Point Slides - Soraya, Kety (Fakultas Keguruan dan Ilmu Pendidikan Universitas Faletehan, 2022)
In the recently, students have to understand multimodal text become understanding so, probing into students' PowerPoint Slides can impact an overview of the students' multimodal literacy. To add to this body of research, the present study attempts to analyze the implementation and logical meaning of six senior high school students' PPT slides, which explain natural and social phenomena. Through the qualitative design, students' PPT focusing on the students' slides capturing the images and texts were collected. These data were analyzed using the concept of the representational meanings of images proposed by Kress & van Leeuwen, the representational meaning of text proposed by Halliday, and the logical meanings of images and text comprising status and logico-semantic relation suggested by Martinec & Salway, which are under the Approach of Systemic Functional Multimodal Discourse Analysis (SF-MDA). The analysis reveals that experientially the Actional processes and the Relational Process are dominantly used in Students' PPT, and logically the complementary relation and logico-semantic of exemplification with Text more general are the most frequent logical meaning realized in Students PPT. The results offer a practical implication and suggestion for further research. The practical implication is that multimodal learning is necessary to emerge in the language instructions for scaffolding the learners' multimodal literacy. Besides, further research is recommended to investigate different and foci of analysis to develop Multimodal Discourse Analysis